a平方-5ab-24b平方-2a+27b-3如何因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 04:38:58
a平方-5ab-24b平方-2a+27b-3如何因式分解a平方-5ab-24b平方-2a+27b-3如何因式分解a平方-5ab-24b平方-2a+27b-3如何因式分解原式=a方-(5b+2)a-(2
a平方-5ab-24b平方-2a+27b-3如何因式分解
a平方-5ab-24b平方-2a+27b-3如何因式分解
a平方-5ab-24b平方-2a+27b-3如何因式分解
原式=a方-(5b+2)a-(24b方-27b+3) =a方-(5b+2)a-3(8b-1)(b-1) =(a-8b+1)(a+3b-3)
(-2a平方)(ab+b平方)-5a(a平方b-ab平方)
a平方-5ab-24b平方-2a+27b-3如何因式分解
(a平方+b平方)平方-(2ab)平方 因式分解
a平方b平方-ab-2因式分解
3a平方;-2ab-b平方; - ( )= -5a + ab - 2b平方.快
a平方b+ab平方分之a平方-b平方除以(2ab分之a平方-b平方-1)
(a-b)平方-2ab(b-a)
(5a平方-3ab+b平方)-(2a平方+3ab-2b平方)的值 其中a平方+b平方=10 ab=3
(5a平方-3ab+b平方)-(2a平方+3ab-2b平方)的值 其中a平方+b平方=10 ab=3 快
5ab平方-{2a平方b-[3ab平方-(4ab平方-2ab平方)]},其中ab满足|a-2|+(b+1)平方=0
若a平方等于5-ab,ab+b平方=2则a平方+2ab+b平方等于
3a的平方b+ 2ab的平方-5ab的平方 6a的平方b ab
-2a平方(1/2ab+b平方)-5a(a平方b-ab平方)
1.16+24(a-b)+9(a-b)平方2.4a-b平方+2a+b3.(a平方+b平方)平方-4a平方b平方4.4a平方b四次方+2ab平方-9c平方-3c5.x三次方+2xy-x-xy平方6.3x平方-10xy+3y平方-x-5y-2
已知a的平方+b的平方-2a+4b+5 ,求a的平方+2ab+b的平方分之a的平方-b的平方
(a平方-b平方)/(a-b) +(2a平方-4ab+2b平方)/(a-b)平方
4(a的平方b-2ab平方)-(a平方b+2ab平方)
4(a的平方b-2ab平方)-(a平方b+2ab平方)?